Effect of Azotobacter sp. and Cow Manure on Nitrogen Availability in Saline Soil, Root Length, and Vitamin C Content of Tomato - Aulifia Nisak Aisyah; Rossyda Priyadarshini; Siswanto Siswanto (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
Nitrogen is a macronutrient for plants, but its availability in saline soil is a limiting factor, making it difficult to cultivate plants. This study aims to examine the effect of the combination of Azotobacter sp. and cow manure in increasing the available N of saline soil, and to obtain the best combination in increasing the growth of tomato plants in saline soil. This research was conducted in the greenhouse and laboratory of UPN "Veteran" Jawa Timur. Saline soil samples came from the Wonorejo Mangrove land, Surabaya. Azotobacter sp. isolates came from the roots of Wonorejo mangrove trees. The study used a Completely Randomized Design with 2 factors with 3 replications. First factor was addition of Azotobacter sp., consisted of A0 (no addition of Azotobacter), and A1 (addition Azotobacter at 107 CFU/mL. Second factor was cow manure (K) involved 4 levels (in ton/ha): A0 (0); K1 (20); K2 (30); K3 (40). The results of this research showed that application of Azotobacter sp. and cow manure affected the parameters of available N, EC, pH and vitamin C content, but did not affect the parameters of plant root length. Combination of Azotobacter 107 CFU/mL + 40 tons/ha of cow manure produced the best available N of 246.48 ppm. The highest vitamin C content was 36.75 mg/g in the treatment of 107 CFU/mL Azotobacter + 30 ton/ha of cow manure. Cow manure decreased soil EC and increased soil pH.